KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU SARANA PRASARANA DI SEKOLAH MENENGAH PERTAMA ISLAM DARUSSA’ADAH GUBUGKLAKAH MALANG - Muhammad Lutfi Saifuddin (STAI Ma'had Aly Al-Hikam Malang, 2019)
Principal's leadership is the process of how the principal in the process of leading or influencing his subordinates to do what he wants with the goals that have been agreed upon together, one of the principals' tasks is to manage school infrastructure, how school infrastructure becomes quality, school infrastructure is said to be of good quality if has met national standards, the purpose of this study is to describe how the leadership of school principals in improving the quality of infrastructure, describe the supporting and inhibiting factors for improving the quality of infrastructure, and describe the factors of how the benefits of improving the quality of infrastructure in Islamic junior high school Darussa'adah. This study uses descriptive qualitative, with research locations in Darussa'adah Gubugklakah Middle School, data collection using interviews, observation, and documentation. Data analysis is performed by reducing the data, then presenting the data, and finally the compiled data is drawn to a conclusion, checking the validity of the data using creatibility which includes persistence of observations, extension of observations, and triangulation. The results of the analysis show that (1) the leadership of school principals in improving the quality of infrastructure in Darussa'adah Islamic Middle School is by processing existing funds to complement the lack of infrastructure, inviting all elements of the teaching staff to work together to complete the required infrastructure, submit proposals- proposals for requests for assistance, and use boss funds to complete infrastructure, (2) supporting factors for improving the quality of infrastructure, namely assistance from the government, support from foundations, and collaboration with committees, (3) The benefits of improving the quality of infrastructure are making it easier for students and also the teachers in teaching and learning activities, making all teaching and learning activities run smoothly, and foster a sense of joy in the school community so as to foster enthusiasm for students to learn.